2012
DOI: 10.1177/0269216312463623
|View full text |Cite
|
Sign up to set email alerts
|

Why do we want the right to die? A systematic review of the international literature on the views of patients, carers and the public on assisted dying

Abstract: Our review sheds light on ordinary people's perspectives about assisted dying, when they are ill or disabled. Unbearable suffering is a key construct, and common factors are revealed that lead people to ask for help to die. The consistency of international views indicates a mandate for legislative and medical systems worldwide to listen and understand this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
127
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(144 citation statements)
references
References 32 publications
9
127
0
8
Order By: Relevance
“…This was highlighted in the case of Sheila, whose desire to die was only partly attributable to her underlying medical condition but also undoubtedly influenced by her relationships, past and present. This finding is confirmed by other studies examining the motivations of people requesting an assisted suicide (Dees et al 2011;Hendry et al 2013). A primary question in the debate about whether assisted suicide should be legalized in the United Kingdom and elsewhere is where the limits of medicine lie in terms of the medical profession's responsibility to relieve suffering, given its phenomenological and intersubjective dimensions.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…This was highlighted in the case of Sheila, whose desire to die was only partly attributable to her underlying medical condition but also undoubtedly influenced by her relationships, past and present. This finding is confirmed by other studies examining the motivations of people requesting an assisted suicide (Dees et al 2011;Hendry et al 2013). A primary question in the debate about whether assisted suicide should be legalized in the United Kingdom and elsewhere is where the limits of medicine lie in terms of the medical profession's responsibility to relieve suffering, given its phenomenological and intersubjective dimensions.…”
Section: Resultssupporting
confidence: 67%
“…These four domains bear similarity to the four dimensions of 'total pain' (physical, mental, social, and spiritual), a concept central to the development of the modern hospice movement (Saunders 2006). The literature suggests that while those who request an assisted suicide are suffering from symptoms of illness or ageing, other factors influencing their quality of life can be important in motivating their desire to die (Hendry et al 2013). These factors include dependency on others; hopelessness; loss of 'self,' meaning or dignity; loneliness or loss of social connectedness; and being tired of life (Hendry et al 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have investigated the factors associated with attitudes towards assisted dying in dementia. The reviewed research consistently indicated an association between age, ethnicity, gender and religion and support for assisted dying in dementia, which is comparable with previous reviews on general assisted dying attitudes (Emanuel, 2002;Hendry et al, 2013). Interestingly, however, this review suggests that aside from religion, these sociodemographic factors are not significantly associated with physician's attitudes and are most frequently linked to public attitudes.…”
Section: Factors Associated With Assisted Dying Attitudessupporting
confidence: 81%
“…Previous systematic reviews have examined general attitudes towards assisted dying and have not specifically reviewed the literature in relation to dementia (Emanuel, 2002;McCormack et al, 2012;Hendry et al, 2013). However, people may hold different attitudes on assisted dying for degenerative diseases, compared with other terminal illnesses (Mitchell, 2004).…”
Section: Previous Reviewsmentioning
confidence: 99%